Influencia de bioestimulantes de crecimiento orgánicos, en dos variedades de Amaranto (Amaranthus spp), originarios de Vniissok (Rusia) para la producción de semilla en la parroquia Picaihua, provincia de Tungurahua, 2021 - Jami Sánchez, José Luis (2021)
In this research, different doses of organic growth biostimulants were evaluated to produce two varieties of amaranth (Valentina and Krepish). The experimental field site was carried out in the Calvario neighborhood of the Picaihua parish located in the Ambato canton. The specific objectives of the research were: To determine the best biostimulant for amaranth seed production, to identify the amaranth variety that adapts to the climatic conditions of the sector, and to select the best plants for the production of F3 seed. A Randomized Complete Block Design was used with a 2x3 +2 factorial arrangement. Where A is the amaranth varieties (Valentina and Krepish), B was considered the organic growth biostimulants (Alga 600, Seaweed Extract, Foliplus). Two, the controls per variety (without biostimulants), with a total of 8 treatments that were arranged in three replications, added during the whole vegetative period, the morphological parameters were evaluated every 15 days obtaining as final results: Stem length, number of leaves, size of inflorescences. During nursery management, all these species germinated thoroughly after five days. In the present investigation the biostimulants did not show significant differences. Possibly this affect is determined by meteorological problems, from the continuous rains that occurred on the days that the biostimulants were applied. The Krepish variety presented better results, with a stem length (71.63 cm), number of leaves (334.33), plant height (92.23 cm) and central inflorescence length (19.91 cm). This result shows a development and improvement in the adaptability processes, which can be compared in the work given by (Guanoluisa, 2017). In the same way, A. tricolor (Valentina), had positive results: stem length (66.38 cm), number of leaves (268.97), plant height (83.74 cm) and central inflorescence length (16.18 cm), in open field conditions, these data are similar to the results of the research obtained in controlled conditions by (Casa, 2017). The best plants were selected to obtain F3 seed, in which 24 plants were collected for the Krepish variety and 20 for Valentina, since they comply with the referred conditions, according to the selected characters such as: greater length of stem and inflorescence, height, and biomass. They will be taken to the field for the studies of F3 seed production during the following year.